Conserved Regions from Neisseria gonorrhoeae Pilin Are Immunosilent and Not Immunosuppressive - Hansen, Johanna K. (American Society for Microbiology, 2007)
PilE is the primary subunit of type IV pili from Neisseria gonorrhoeae and contains a surface-exposed hypervariable region thought to be one feature of pili that has prevented development of a pilin-based vaccine. We have created a three-dimensional structure-based antigen by replacing the hypervariable region of PilE with an aspartate-glutamine linker chosen from the sequence of Pseudomonas aeruginosa PilA. We then characterized murine immune responses to this novel protein to determine if conserved PilE regions could serve as a vaccine candidate. The control PilE protein elicited strong T-cell-dependent B-cell responses that are specific to epitopes in both the hypervariable deletion and control proteins. In contrast, the hypervariable deletion protein was unable to elicit an immune response in mice, suggesting that in the absence of the hypervariable region, the conserved regions of PilE alone are not sufficient for antibody production. Further analysis of these PilE proteins with suppressor cell assays showed that neither suppresses T- or B-cell responses, and flow cytometry experiments suggested that they do not exert suppressor effects by activating T regulatory cells. Our results show that in the murine model, the hypervariable region of PilE is required to activate immune responses to pilin, whereas the conserved regions are unusually nonimmunogenic. In addition, we show that both hypervariable and conserved regions of pilin are not suppressive, suggesting that PilE does not cause the decrease in T-cell populations observed during gonococcal cervicitis.